Uniformity and Collimation of Incoherence Gaussian Beam With Divergence Based on Only One Fresnel Surface - C. M. Tsai (IEEE Photonics Journal, 2016)
An incoherence Gaussian beam with divergence is converted to uniformity and collimation simultaneously at a desirable spot size requirement by using one Fresnel surface. The design process is simplified to one-dimension (1-D) with respect to the incoherence Gaussian beam having revolution symmetry. Such a 1-D Gaussian profile is divided into several parts from the center to the outside. The divided power corresponds to a height difference, i.e., to provide uniformity, the power to the corresponding height difference ratio is constant. The ray passing through the boundary of each part is regarded as the incident ray that would be refracted to run parallel to the optical axis through a piece of surface designed for implementing collimation. An incoherence collimated Gaussian beam is demonstrated to verify the conversion beam with uniformity and collimation simultaneously. The simulation results show that the uniformity is around 95% and the collimation is less than 0.1°.